Sustainability factors underlying traditional grazing in Mount Rinjani National Park, West Nusa Tenggara, Indonesia - Metananda, Arya Arismaya; Suhubdy; Mertha, I Gde; Soekardono; AR, Nur Hasnah; Afrianto, Whisnu Febry (Ethnobotany Research and Applications, 2025)
Background: Traditional grazing in Mount Rinjani National Park (MRNP), West Nusa Tenggara, Indonesia, is a crucial livelihood practice for local communities. However, it poses ecological challenges such as overgrazing, habitat degradation, and an increased wildfire risk. Understanding the sustainability of grazing requires an integrated assessment of ecological, social, economic, and institutional factors. Methods: This study employed the MICMAC method to analyze key sustainability variables and their interdependencies. Data collection included expert judgment, interviews with local farmers and stakeholders, field surveys, and secondary data analysis. A structured influence-dependence matrix was used to classify variables based on their role in the grazing system. Results: The quadrant analysis identifies key factors influencing grass utilization in MRNP. Determinant variables such as vegetation cover (C1), land area (C4), grass use (C6), use frequency (C8), and use pattern (C7) play a major role in shaping grazing sustainability. Linkage variables, including institutional factors (C9) and demographics (C5), highlight the importance of governance and community dynamics. Other factors significantly influence the dependent variables, whereas autonomous variables, such as wildlife habitat (C2) and carrying capacity (C3), have minimal interaction with the system. These findings emphasize the need for an integrated approach to balancing grazing activities and conservation efforts in MRNP. Conclusions: Sustainable grazing management in MRNP requires a collaborative approach that integrates community participation, institutional support, and conservation strategies. Fire prevention, controlled livestock management, and the rehabilitation of degraded grasslands are necessary interventions. Future policies should balance ecological conservation with local economic needs to ensure long-term sustainability. Keywords: Grazing, MICMAC, Mount Rinjani National Park, Natural resources, Sustainability Abstrak Background: Penggembalaan tradisional di Taman Nasional Gunung Rinjani (TNGR), Nusa Tenggara Barat, Indonesia, merupakan praktik mata pencaharian penting bagi masyarakat lokal. Namun, praktik ini menimbulkan tantangan ekologis seperti penggembalaan berlebihan (overgrazing), degradasi habitat, dan peningkatan risiko kebakaran hutan. Untuk memahami keberlanjutan penggembalaan, diperlukan penilaian yang terintegrasi dari aspek ekologi, sosial, ekonomi, dan kelembagaan. Methods: Penelitian ini menggunakan metode MICMAC untuk menganalisis variabel-variabel utama yang mempengaruhi keberlanjutan penggembalaan serta keterkaitannya. Pengumpulan data dilakukan melalui penilaian ahli, wawancara dengan petani dan pemangku kepentingan, survei lapangan, serta analisis data sekunder. Matriks pengaruh-ketergantungan yang terstruktur digunakan untuk mengklasifikasikan variabel berdasarkan perannya dalam sistem penggembalaan. Results: Analisis kuadran mengidentifikasi faktor utama yang mempengaruhi pemanfaatan padang rumput di TNGR. Variabel determinan seperti tutupan vegetasi (C1), luas lahan (C4), penggunaan rumput (C6), frekuensi pemanfaatan (C8), dan pola penggunaan (C7) memiliki peran utama dalam keberlanjutan penggembalaan. Variabel penghubung seperti faktor kelembagaan (C9) dan demografi (C5) menunjukkan pentingnya tata kelola dan dinamika komunitas. Variabel dependen sangat dipengaruhi oleh faktor lain, sedangkan variabel otonom, seperti habitat satwa liar (C2) dan daya dukung habitat (C3), memiliki interaksi minimal dengan sistem. Temuan ini menekankan perlunya pendekatan terpadu untuk menyeimbangkan aktivitas penggembalaan dan upaya konservasi di TNGR. Conclusions: Pengelolaan penggembalaan berkelanjutan di TNGR memerlukan pendekatan kolaboratif yang mengintegrasikan partisipasi masyarakat, dukungan kelembagaan, dan strategi konservasi. Upaya pencegahan kebakaran, pengelolaan ternak yang terkendali, serta rehabilitasi padang rumput yang terdegradasi menjadi langkah penting. Kebijakan ke depan harus berfokus pada keseimbangan antara konservasi ekologi dan kebutuhan ekonomi lokal untuk memastikan keberlanjutan jangka panjang. Keywords: Penggembalaan, MICMAC, Taman Nasional Gunung Rinjani, Sumber daya alam, Keberlanjutan